CYBERSECURITY AND DATA PROTECTION LAWS IN INDIA: CHALLENGES AND PROSPECTS - Bhattacharya, Gargi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In an increasingly digitized world, the protection of personal data and the assurance of cyber security have emerged as fundamental legal and ethical imperatives. Privacy, long recognized as a core human right, has evolved from the classical notion of “the right to be let alone” to encompass the protection of personal information in digital spaces. This paper examines the evolution of data privacy and protection laws globally and within India, tracing their development from early international instruments such as the Universal Declaration of Human Rights (1948) and the European Convention on Human Rights (1950) to modern frameworks like the OECD Guidelines (1980) and the European Union’s General Data Protection Regulation (GDPR). The study highlights the progressive recognition of informational privacy as an extension of constitutional rights under Article 21 of the Indian Constitution, particularly following the landmark judgment in Justice K.S. Puttaswamy v. Union of India (2017).